Enhancing soybean productivity through agroforestry, organic waste fertilization, and mulching: A review about climate change - Wahidurromdloni Fauzan; Theresia Sri Budiastuti Maria; Supriyono (BIO Web of Conferences)
Some issues that will threaten agriculture now and in the future are declining productivity and increased risks due to climate change. However, agroforestry, organic waste fertilizers, and mulching are promising ways to address these challenges. They offer approaches that increase productivity and improve land adaptability to climate extremes. This review explores the integration of agroforestry, organic fertilizer from local waste and mulching systems as strategies to increase soybean productivity while ensuring sustainability. Agroforestry reduced soil erosion by 50% and increased soil carbon stocks by 26-34% at various depths. Organic fertilizers combined with inorganic inputs increased yields by 12.8-32.5%, while mulching further increased yields by 38.6-44.2%. These practices improve soil health, reduce reliance on chemical inputs and provide ecosystem services that support adaptation and mitigation strategies for climate change. This combination is expected to increase soybean production to meet global demand. However, adoption remains limited due to economic and technical constraints, particularly among smallholder farmers. Future studies should address cost-effective solutions and identify optimal zones for implementation.